Cationic Porphyrins as Telomerase Inhibitors: the Interaction of Tetra-(N-methyl-4-pyridyl)porphine with Quadruplex DNA - Wheelhouse, Richard T; Sun, Daekyu; Han, Haiyong; Han, Frank Xiaoguang; Hurley, Laurence H (Journal of the American Chemical Society, 1998)
Telomerase presents a potentially selective target for the design of new antitumor drugs. The structure of the telomerase protein remains elusive (although recently shown to be related to other reverse transcriptases), and in consequence, the design of telomerase inhibitors has hitherto been restricted to antisense strategies directed toward binding or cleaving the template sequence of the telomerase RNA or established strategies for inhibiting reverse transcriptases. Several unique nucleic acid structures are associated with the telomerase reaction cycle, and a notable achievement has been the targeting of quadruplex DNA and its validation as a receptor for the structure-based design of nonnucleotide telomerase inhibitors. We supposed that 5,10,15,20-tetra-(N-methyl-4-pyridyl)porphine (TMPyP4) was of appropriate size to stack with the G-tetrads that stabilize quadruplex DNA. Herein we report how this porphyrin interacts with human telomeric quadruplexes, stabilizes quadruplex DNA to thermal denaturation, and inhibits human telomerase in a cell-free system.